The boundless sea : self and history - Okihiro, Gary Y., 1945- (University of California Press, 2019)
"The last book in a trilogy of explorations on space and time from a preeminent scholar, The Boundless Sea is Gary Y. Okihiro's most innovative yet. Whereas Okihiro's previous books, Island World and Pineapple Culture, sought to deconstruct islands and continents, tropical and temperate zones, this book interrogates the assumed divides between space and time, memoir and history, and the historian and the writing of history. Okihiro uses himself--from Okinawan roots, growing up on a sugar plantation in Hawai'i, researching in Botswana, and teaching in California--to reveal the historian's craft involving diverse methodologies and subject matters. Okihiro's imaginative narrative weaves back and forth through decades of time and across vast spatial and societal differences, theorized as historical formations, to critique history's conventions. Taking its title from the author's surname, The Boundless Sea is a deeply personal and reflective volume that challenges how we think about time and space, notions of history"--Provided by publisher.